Postoperative pain of single-visit endodontic treatment with gutta-percha versus MTA filling: a randomized superiority trial - Masoud Khabiri; Sahel Kamgar; Pedram Iranmanesh; Abbasali Khademi; Mahmoud Torabinejad (BMC, 2023)
Abstract Background Postoperative pain has remained a challenge for clinicians. This randomized superiority trial compared the levels of postoperative pain following the use of gutta-percha (GP) and sealer or mineral trioxide aggregate (MTA) as root canal filling materials in teeth with asymptomatic apical periodontitis. Methods A total of 119 patients were initially evaluated in this two-arm, parallel-group, single-blind, superiority randomized trial. The inclusion criteria were participants aged 18-65 years with single-canal premolars diagnosed with asymptomatic apical periodontitis. The participants were finally divided into two groups using the permuted block randomization method. In the GP group (N = 46), the cleaned and shaped root canals were filled with gutta-percha and AH Plus sealer, while in the MTA group (N = 48), the cleaned and shaped root canals were filled with an MTA apical filling and a coronal gutta-percha and sealer. Patient pain level was measured 6, 12, 24, 48, and 72 h postoperatively using a 10-point visual analog scale (VAS). The data were analyzed by the chi-square, independent t, Friedman, and Mann-Whitney U tests. Results The mean of VAS scores decreased significantly over time in both groups (P < 0.001). The mean VAS scores were significantly lower in the MTA filling group than in the other group (P < 0.05). Female patients reported higher VAS scores at 6- and 12-hour periods in both groups (P < 0.05). Conclusion MTA as a root canal filling material might be a valuable option for clinicians due to its low postoperative pain. Trial registration The trial protocol was registered at the Registry of Clinical Trials (IRCT20191104045331N1).